Foreign ownership, technological capabilities, and clothing exports in Sri Lanka - Ganeshan Wignaraja (Asian Development Bank Institute (ADBI), 2007)
Drawing on recent developments in applied international trade and innovation and learning in developing countries, this paper examines the links between firm-level export performance, foreign ownership, and the acquisition of technological capabilities in a sample of 205 clothing enterprises in Sri Lanka. Econometric analysis indicates that foreign ownership, firm size, human capital, technological capabilities, and geographical location are all positively associated with export shares. Furthermore, higher levels of technological capability are associated with larger firm size, university-level manpower, and R&D. Microlevel investigations are a complementary input to developing policies for promoting private sector competitiveness in outward-oriented developing countries.
Keywords: F14; O31; L67; 330; Direktinvestition; Bekleidungsindustrie; Exportindustrie; Wirtschaftsreform; Sri Lanka; Investitionsklima